Pengaruh Komunikasi, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan pada Bagian Produksi Pabrik Rokok Cengkir Gading Nganjuk - Bayu Cakra Wijaya; Trisnia Widuri; Kukuh Harianto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study was conducted to evaluate and confirm hypotheses related to communication, work discipline, and work environment as determinants of employee performance at Pabrik Rokok Cengkir Gading Nganjuk. A quantitative approach with an associative method was adopted. The research utilized a non-probability sampling strategy, specifically the saturated sample method, by involving all 53 employees in the production section. Data were processed using SPSS version 26 and analyzed through validity, reliability, normality, linearity, multicollinearity, heteroscedasticity, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Findings indicate that communication has a positive but insignificant effect on performance (Sig. 0.131 > 0.05). In contrast, work discipline significantly and positively influences performance (Sig. 0.016 < 0.05), while the work environment has a positive but insignificant effect (Sig. 0.052 > 0.05). On the other hand, communication, work discipline, and work environment together significantly affect employee performance (Sig. 0.000 < 0.05). The overall contribution of these three independent variables is 47.9%, with the remaining 52.1% explained by other unobserved variables.